Succinate induces skeletal muscle fiber remodeling via SUCNR1 signaling. (18th July 2019) - Wang, Tao; Xu, Ya‐Qiong; Yuan, Ye‐Xian; Xu, Ping‐Wen; Zhang, Cha; Li, Fan; Wang, Li‐Na; Yin, Cong; Zhang, Lin; Cai, Xing‐Cai; Zhu, Can‐Jun; Xu, Jing‐Ren; et al.
Abstract: The conversion of skeletal muscle fiber from fast twitch to slow‐twitch is important for sustained and tonic contractile events, maintenance of energy homeostasis, and the alleviation of fatigue. Skeletal muscle remodeling is effectively induced by endurance or aerobic exercise, which also generates several tricarboxylic acid (TCA) cycle intermediates, including succinate. However, whether succinate regulates muscle fiber‐type transitions remains unclear. Here, we found that dietary succinate supplementation increased endurance exercise ability, myosin heavy chain I expression, aerobic enzyme activity, oxygen consumption, and mitochondrial biogenesis in mouse skeletal muscle. By contrast, succinate decreased lactate dehydrogenase activity, lactate production, and myosin heavy chain IIb expression. Further, by using pharmacological or genetic loss‐of‐function models generated by phospholipase Cβ antagonists, SUCNR1 global knockout, or SUCNR1 gastrocnemius‐specific knockdown, we found that the effects of succinate on skeletal muscle fiber‐type remodeling are mediated by SUCNR1 and its downstream calcium/NFAT signaling pathway. In summary, our results demonstrate succinate induces transition of skeletal muscle fiber via SUCNR1 signaling pathway. These findings suggest the potential beneficial use of succinate‐based compounds in both athletic and sedentary populations. Synopsis: Aerobic exercise leads to skeletal muscle remodelling. This study reveals that dietary succinate is sufficient to elicit muscle remodelling and increased endurance in sedentary mice. Dietary succinate increases endurance exercise ability in mice. Dietary succinate induces skeletal muscle fiber transition from fast‐twitch to slow‐twitch. SUCNR1 signaling pathway is required for the succinate induced skeletal muscle remodeling. Abstract : Aerobic exercise leads to skeletal muscle remodelling. This study reveals that dietary succinate is sufficient to elicit muscle remodelling and increased endurance in sedentary mice.